1
$\begingroup$

This is a bit embarrassing, but I'm struggling to evaluate this sum.

\begin{equation}\sum_{m=0}^{2k} \frac{x^{m}}{(2k-m)!}\end{equation}

The coefficients are nearly the binomial coefficients, but with an $m!$ missing. (The $(2k)!$ could just be added by hand).

Any pointers?

$\endgroup$
  • 2
    $\begingroup$ Have you tried summing backwards, i.e., changing the iterator from m to 2k - n ? $\endgroup$ – Lucian Oct 24 '16 at 5:02
2
$\begingroup$

Consider the series in the following way: \begin{align} \sum_{m=0}^{2k} \frac{x^{m}}{(2k-m)!} &= \frac{x^{0}}{(2k)!} + \cdots + \frac{x^{2k-1}}{1!} + \frac{x^{2k}}{0!} \\ &= \sum_{m=0}^{2k} \frac{x^{2k-m}}{m!} \\ &= x^{2k} \, e_{2k}\left(\frac{1}{x}\right), \end{align} where the $e_{n}(x)$ is the finite exponential functions given by $$e_{n}(x) = \sum_{k=0}^{n} \frac{x^{k}}{k!}.$$

$\endgroup$
2
$\begingroup$

A too long comment, I guess.

Starting from Leucippus's answer, the result could simplify using the incomplete gamma function, leading to

$$\sum_{m=0}^{2k} \frac{x^{m}}{(2k-m)!}=\sum_{m=0}^{2k} \frac{x^{2k-m}}{m!}= e^{\frac{1}{x}} \frac{x^{2 k} }{(2 k)!}\,\Gamma \left(2 k+1,\frac{1}{x}\right)$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.